A motorist traveled 311 miles on 12 gallons of gas. To the nearest tenth, how many miles can the motorist travel on one gallon of gas?

Answers

Answer 1
Answer: we know that
by using proportion
(311 miles)/(12 gallons) = (x miles)/(1 gallon)  \n x= (31.1)/(12)  \n x=25.9 miles

the answer is
25.9 miles
Answer 2
Answer: Number of miles that can be traveled on one gallon of gas=311/12
                                                                                           =25.92miles
                                                                                 =25.9miles(to the nearest tenth)

Related Questions

A box contains 4 oranges, 9 apples, and 3 pears. Liliana selects a piece of fruit from the box at random.What is the probability that she selects an orange or a pear? A.1 over 20 B.3 over 64 C.7 over 16 D.9 over 16
What is the pattern?6+4= 210 9+2= 711 8+5- 313 5+2= 37 7+6= 113 9+8= 117 10+6= 416 15+3= 1218
PLEASEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEE HELPPPPPPPPPPPPPPPPP
6+(6-2)x6 I DONT GET ITTT
I have class in a half an hour and I still haven't solved all of the hw questions... please help guys I'll give 90 points and brainliest for the first correct answer with brief explanation: thank you SOOOOOOOOOO much!Given: E, F, Q, D∈k(O),O ∈ ED, m∠DFQ = 10°, measure of arc EF = 28° Find: Angles of △EFQ

Solve the algebraic expression n+8 if n = 15

Answers

If n=15 you do 15+8 which equals 23. Hope that helped. ✌
Seeing that n=15, we can say 15+8=23. So the final answer is 23.

What is the factored form of 27d^6+8g^12?

Answers

Answer

(3d² + 2g⁴)(9d⁴ - 6d²g⁴ + 4g⁸)


Explanation

We can factor out the following equation as follows:

27d⁶ + 8g¹² = 3³d⁶ + 2³g¹²

               = (3d²)³ + (2g⁴)³

                = (3d² + 2g⁴)((3d²)² - 3d²2g⁴ + (2g⁴)²)

               =  (3d² + 2g⁴)(9d⁴ - 6d²g⁴ + 4g⁸)

I hope this helps you

What is the inverse of the function f(x) = x +3?A. h(x) =1/3 x + 3
B. h(x) = 1/3x – 3
C. h(x) = x – 3
D. h(x) = x + 3

Answers

Answer:

Option C is correct that is h(x)=x-3

Step-by-step explanation:

We have been given a function:

f(x)=x=3

\text{let y}=f(x)

y=x+3

x=y-3

Hence,f^(-1)y=y-3

Therefore, f^(-1)x=x-3

Hence, Option C is correct that is h(x)=x-3

f(x) = x + 3
y = x + 3
x = y - 3

Inverse is h(x) = x - 3

What is 1 1/2 minus 1/4

Answers

An 1 1/2 minus 1/4 is equal to 1 1/4 or 1.25 as a decimal.

To subtract fractions, they must have a common denominator the common denominator is 4. Let's find the equivalent fractions with a denominator of 4:

1 1/2 is the same as 1 + 1/2, and convert 1/2 to have a denominator of 4:

1 + 1/2 = 1 + 2/4

Now, subtract 1/4:

(1 + 2/4) - 1/4 = 1 + (2/4 - 1/4) = 1 + 1/4

To know more about  decimal here

brainly.com/question/33109985

#SPJ6

1 1/2 - 1/4
You have to have a common denominator which is 4 in this istance.
That makes it 1 2/4 - 1/4. That equals 1 3/4.


Hope that this helped! :)

Does anyone know where to plot this?

Answers

Answer:

(-3,1) becomes (1,-1)

(-4,7) becomes (0,5)

(-6,3) becomes (-2,1)

(-9,8) becomes (-5,6)

Step-by-step explanation:

just move every point 4 to the right and 2 down. once you plot the new points draw and connect

What is the first step when rewriting y = –4x2 + 2x – 7 in the form y = a(x – h)2 + k?A.2 must be factored from 2x – 7

B.–4 must be factored from –4x2 + 2x

C.x must be factored from –4x2 + 2x

D.–4 must be factored from –4x2 – 7

Answers

complete the square

first, the coeieicne infront of x^2 term musbe 1
so if you have
y=ax^2+bx+c
isolate x terms and undistribute a
y=a(x^2+(b/a)x)+c

B is answer

Answer:

B

Step-by-step explanation:

Right on Edge